Study on the Structural Design and Control of Modular Magnetic Suction Five-finger Dexterous Hand - Chengjun Si (Jixie chuandong)
In order to solve the problems of low freedom of five fingers dexterous hand and complicated disassembly and installation， a modular， easy disassembly and installation， direct drive 11 degrees of freedom five fingers dexterous hand is designed. Each finger joint has a rotation range of at least ±90°. Through the special design of the rotation angle of the thumb， the left/right hand mode of the dexterous hand can be directly switched and both sides can be grasped at the same time. A five-finger dexterous hand prototype is made through 3D printing. Aiming at the complex control system caused by multiple sensors of the dexterous hand at present， the current feedback control algorithm is proposed， through signal acquisition and post-processing of the motor drive current， the mathematical model of current-rotation angle-fingertip force is established， and the grasping experiment is carried out. The results show that the designed modular dexterous hand has strong grasping ability， and the control algorithm of current feedback can control the movement state and grasping force of the dexterous hand， and complete the target grab operation.